2020
DOI: 10.1007/s00262-020-02570-3
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus (EBV) and polyomaviruses are detectable in oropharyngeal cancer and EBV may have prognostic impact

Abstract: Background The etiological role of human papillomavirus (HPV) in oropharyngeal squamous cell carcinoma (OPSCC) is confirmed. However, the role of other oncoviruses in OPSCC is unknown. Materials and methods A total of 158 consecutive OPSCC patients treated with curative intent were included. DNA extracted from tumor sections was used to detect Epstein-Barr virus (EBV), HPV, and the following polyomaviruses: John Cunningham virus (JCV), Simian virus 40 (SV40), and BK virus (BKV) with PCR. In addition, p16 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…12 A recent study reported that patients with EBV-encoded small RNA (EBER)-positive oropharyngeal squamous cell carcinoma (OPSCC) had significantly poorer OS, DFS and prognosis than those with HPV-positive OPSCC. 13 So, we hypothesis that the identified RBPs may play an indispensable role in EBV-related HNSCC and needs more researches to conduct.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent study reported that patients with EBV-encoded small RNA (EBER)-positive oropharyngeal squamous cell carcinoma (OPSCC) had significantly poorer OS, DFS and prognosis than those with HPV-positive OPSCC. 13 So, we hypothesis that the identified RBPs may play an indispensable role in EBV-related HNSCC and needs more researches to conduct.…”
Section: Discussionmentioning
confidence: 99%
“…Other viruses have been identified in OSCC samples, as individual infections or in co-infection with HPV. Still, their role in the disease is unclear (124)(125)(126)(127). Despite its importance, HPV-unrelated OSCC cases account for the vast majority of oral cancer cases.…”
Section: The Microbiome and Oral Cancermentioning
confidence: 99%
“…HNSCC displays a high grade of heterogeneity [ 2 ]. It can be attributed to the diversity of manifestation sites in the upper aerodigestive tract and the different etiologic backgrounds, including tobacco or alcohol consumption [ 3 ] and virus infection [ 4 ]. Consequently, the response of patients to multimodal treatment, including surgery and/or radio(chemo)therapy exhibits similar diversity.…”
Section: Introductionmentioning
confidence: 99%